The Semantic Web: ESWC 2012 Satellite Events ESWC 2012 Satellite Events, Heraklion, Crete, Greece, May 27-31, 2012. Revised Selected Papers - Simperl, Elena; Norton, Barry; Mladenic, Dunja; Della Valle, Emanuele; Fundulaki, Irini; Passant, Alexandre; Troncy, Raphaël; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-proceedings of the satellite events of the 9th International Conference on the Semantic Web, ESWC 2012, held in Heraklion, Crete, Greece, in May 2012. This volume contains 49 full papers  and 13 short papers describing the posters and demonstrations. (SUGGESTION/ HELP  needed).
Best Workshop Papers -- Finding Concept Coverings in Aligning Ontologies of Linked Data -- Extraction of Historical Events from Wikipedia -- Capturing Interactive Data Transformation Operations using Provenance Workflows -- Representing Interoperable Provenance Descriptions for ETL Work Flows -- Using SPIN to formalise XBRL Accounting Regulations on the Semantic Web -- An ontology-based opinion mining approach for the Financial domain -- Interacting with Statistical Linked Data via OLAP Operations -- Linguistic Modeling of Linked Open Data for Question Answering -- SPARTIQULATION: Verbalizing SPARQL queries -- Multilingual Ontology Matching Evaluation - A First Report on using Multi Farm -- Evaluating Semantic Search Systems to Identify Future Directions of Research -- The DyKOSMap approach for analyzing and supporting the mapping maintenance problem in biomedical Knowledge Organization Systems -- Effective Composition of Mappings for Matching Biomedical Ontologies -- Semantic Interoperability between Clinical Research and Healthcare: the PONTE approach -- A linked data framework for Android -- The Web of Radios - Introducing African Community Radio as an interface to the Web of Data -- Social Media Matrix. Matching Corporate Goals with External Social Media Activities -- Knowledge Modeling of On-line Value Management -- Online open neuroimaging mass meta-analysis with a wiki -- Linked Data and Linked APIs: Similarities, Differences, and Challenges -- Hyperdata: Update APIs for RDF Data Sources (Vision Paper) -- Enabling Semantic Search in Large Open Source Communities -- An Approach for Efficiently Combining Real-time and Past Events for Ubiquitous Business Processing -- Context Management in Event Marketplaces -- SDDS based Hierarchical DHT Systems for an Efficient Resource Discovery in Data Grid Systems -- FaCETa: Backward and Forward Recovery for Execution of Transactional Composite WS -- Poster Session -- A LarKC Approach to Development of Service-Oriented Semantic Reasoning Applications -- Named Entity Disambiguation using Linked Data -- Sharing and Analyzing Remote Sensing Observation Data for Linked Science -- ANISE: an ANatomic SEmantic Visualizer -- RESTdescA Functionality-Centered Approach to Semantic Service Description and Composition -- Bringing the Web of Data to Developing Countries: Linked Market Data in the Sahel -- Leveraging the Emergent Semantics in Twitter Lists for Ontology Development -- Full-text Support for Publish/Subscribe Ontology Systems -- Distributed Stream Reasoning -- ParkJam: Crowdsourcing Parking Availability Information with Linked Data (Poster) -- APA VIVO: A Semantic Framework for Scholarly Identity and Trusted Attribute Exchange -- SciNet: Augmenting Access to Scientific Information -- Managing Contextualized Knowledge with the CKR -- Demonstration Session -- Sgvizler: A JavaScript Wrapper for Easy Visualization of SPARQL Result Sets -- Exploring History through Newspaper Archives -- Semantic Content Management with Apache Stanbol -- RDFaCE-Lite: a WYSIWYM editor for user-friendly semantic text Authoring -- ParkJam: Crowdsourcing Parking Availability Information with Linked Data -- Nobody Wants to Live in a Cold City where no Music Has Been Recorded - Analyzing Statistics with Explain-a-LOD -- Science WISE: A Web-based Interactive Semantic Platform for Paper Annotation and Ontology Editing -- Developing an Incomplete Reasoner in Five Minutes: the Large Knowledge Collider in Action -- Did you validate your ontology? OOPS! -- Does it fit? KOS evaluation using the ICE-Map Visualization -- A Demo for Efficient Human Attention Detection based on Semantics and Complex Event Processing -- Domain-Specific OWL Ontology Visualization with OWLGrEd -- Product customization as Linked Data: demonstration -- Karma: A System for Mapping Structured Sources into the Semantic Web -- Personalized Environmental Service Configuration and Delivery Orchestration: The PESCaDO Demonstrator -- Supporting Rule Generation and Validation on Environmental Data in EnStreaM -- Linked Open Data University of Muenster - Infrastructure and Applications -- OntoPartS: a tool to select part-whole relations in OWL ontologies -- Hubble: Linked Data Hub for Clinical Decision Support -- Confomaton: A Conference Enhancer with Social Media from the Cloud -- OBA: Supporting Ontology-Based Annotation of Natural Language Resources -- HadoopSPARQL: A Hadoop-based Engine for Multiple SPARQL Query Answering -- DEFENDER: a DE composer For quEries agaiNst federations of Endpoints.
Keywords: Information storage and retrieval; Artificial intelligence; Database management; Application software; Information Storage and Retrieval; Artificial Intelligence; Database Management; Information Systems Applications (incl. Internet).